Experiential purchases and feeling autonomous: Their implications for gratitude and ease of justification - Rogelio Puente-Diaz; Judith Cavazos-Arroyo (Frontiers in Psychology, 2023)
In four studies, we tested the influence of type of purchase on autonomy support and the relationships between autonomy support, gratitude, and ease of justification. In each of the three studies, participants were randomly assigned to either the experiential purchase condition or the material purchase condition. In our fourth and last study, participants were assigned to an either autonomy supportive purchase condition or ordinary purchase condition. Results from study 1 showed a positive direct influence of experiential purchases on autonomy support and a direct and indirect significant relationship with gratitude. Results from study 2 with a sample of older consumers showed a positive influence of experiential purchases on autonomy support and a direct and indirect positive relationship with gratitude. In study 3, consumers who brought to mind an expensive experiential purchase reported higher autonomy support than participants who brought to mind an expensive material purchase and this experimental effect had an indirect positive relationship with gratitude and ease of justification. Last, consumers who brought to mind a purchase that truly reflected who they were reported higher levels of autonomy support than consumers who reported an ordinary purchase and this elicited autonomy had a positive relationship with gratitude. The implications of the results were discussed.